2004
DOI: 10.1111/j.1464-5491.2004.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic painful peripheral neuropathy in an urban community: a controlled comparison of people with and without diabetes

Abstract: CPPN is common, often severe but frequently unreported and inadequately treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
271
1
16

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(299 citation statements)
references
References 34 publications
11
271
1
16
Order By: Relevance
“…Neuropathic pain develops in >30% of these patients, meaning that approximately one in six patients with diabetes develops a painful neuropathy [188][189][190] . Several drugs are approved for treatment of neuropathic pain in diabetes, but these drugs do not address the underlying pathogenic mechanisms.…”
Section: Schwann Cells In Diabetic Neuropathymentioning
confidence: 99%
“…Neuropathic pain develops in >30% of these patients, meaning that approximately one in six patients with diabetes develops a painful neuropathy [188][189][190] . Several drugs are approved for treatment of neuropathic pain in diabetes, but these drugs do not address the underlying pathogenic mechanisms.…”
Section: Schwann Cells In Diabetic Neuropathymentioning
confidence: 99%
“…Cardiovascular mortality and morbidity rates in diabetics have been reported by several studies as 2-4 times higher than in non-diabetic subjects. Different studies also indicate that foot ulcers in diabetic patients are linked to a higher mortality [13][14][15][16][17] . Furthermore diabetic foot represents an independent risk factor of morbidity in diabetic patients with a twice mortality rate due to cardiovascular disease in diabetic subjects with foot ulceration compared to those without foot ulceration [16,17] .…”
Section: Cardiovascular Morbidity In Patients With Dfsmentioning
confidence: 99%
“…In patients with an ABI < 0.90, the relative risk has been reported to be 1.25 (95%CI: 1.05, 1.47) for developing an ulcer vs diabetic patients with a normal ABI [14] . Lower limb ischaemia due to proximal arterial occlusive atherosclerosis is an important cause able to predispose to ulceration in more than 30% of cases [15] . Nevertheless a recent study reported that diabetic patients with PAD are more likely in comparison to non-diabetic subjects to have a distal occlusive arterial disease and an higher incidence of amputions and death related to cardiovascular causes [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly reported form of neuropathy is polyneuropathy, also called diabetic peripheral neuropathy, a common and debilitating complication of diabetes (2). Pain in the feet characterized as sharp, stabbing, or burning is observed in 16 -26% of diabetic patients (3,4). They also may complain of pain in response to normally nonpainful stimuli (allodynia).…”
mentioning
confidence: 99%